PEMBANGUNAN APLIKASI SELEKSI PESERTA DIDIK BARU SMK2 SURAKARTA DENGAN METODE AGILE EXTREME PROGRAMMING - Arief Nur Huda; Faisal Najib; Hidayat Abdul Rouf; Rini Anggrainingsih; Viki Dwi Kusnandar (Lembaga Penelitian Universitas Trisakti, 2017)
This paper reports development an admission new students application for support selection process in SMKN 2 Surakarta.Software development model for this application used Waterfall method through stages of analysis, design, implementation and testing phases.Testing on correctness factor showed that this application qualifies user requirement specification of SMK N 2 Surakarta. Testing on reliability factor performed using Apache JMeter software and obtained the result that as many as 20 users did not experience a failure accessing applications simultaneously, whereas the